Explosions, Burn Injuries and Adverse Health Effects of Electronic Nicotine Delivery Systems: A Review of Current Regulations and Future Perspectives - Ayesha Rahman Ahmed; Beverly Etchey; Mahiba Ahmed (Frontiers Media S.A., 2021)
Purpose: While there is a declining trend in the use of traditional methods of smoking tobacco, electronic nicotine delivery systems (ENDS) have gained popularity worldwide. ENDS are marketed as safe for the primary reason that they do not contain the well-established toxic ingredients found in traditional cigarettes. However, growing concerns over incidences of fire and explosion with specific types of ENDS, as well as their short and long-term effects, remain unaddressed. This review examines the under studied role of customized components such as batteries, e-liquid compositions, and methods of nicotine delivery that result in physical injuries and adverse health effects of ENDS. Methods: Using online reference databases (Web of Science, PubMed, Medline other, Google scholar, FDA website, FDA register), we analyzed the mechanisms through which ENDS may pose significant risk to human health. Results: An increase in the use and popularity of ENDS has been observed among youth and adults in the United States since 2007. The ENDS devices available to the public allow for custom alterations which can introduce incompatible components, resulting in overheating and explosion related injuries. Heavy metals have been found to leach from some devices into the e-liquid, and the heating of e-liquid ingredients can produce toxic byproducts. Conclusions: Overall, the current literature demonstrates that ENDS are not a safe alternative to traditional cigarettes due to explosion risks and negative health effects including addiction, adverse respiratory and cardiovascular effects, heavy metal leaching, and toxic byproducts exposure. These risks warrant regulation of ENDS devices and formulations, with urgency underscored by their increasing popularity among youth and adults.